2021
DOI: 10.1002/elps.202100024
|View full text |Cite
|
Sign up to set email alerts
|

A low‐cost and high‐throughput benchtop cell sorter for isolating white blood cells from whole blood

Abstract: The ability to isolate and purify white blood cells (WBCs) from mixed ensembles such as blood would benefit autologous cell-based therapeutics as well as diagnosis of WBC disorders. Current WBCs isolation methods have the limitations of low purity or requiring complex and expensive equipment. In addition, due to the overlap in size distribution between lymphocytes (i.e., a sub-population of WBCs) and red blood cells (RBCs), it is challenging to achieve isolation of entire WBCs populations. In this work, we dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…After Puriogen cell wash, the total count of live cells was changed from 1.53 × 10 6 to 1.34 × 10 6 . Considering the recovery ratio, the influence on the cell viability by Puriogen is below 1%, very similar to our previous cell viability analysis after size-based cell sorting . It is noted that the percentage of dead cells is decreased from 15.2 to 7.72%.…”
Section: Results and Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…After Puriogen cell wash, the total count of live cells was changed from 1.53 × 10 6 to 1.34 × 10 6 . Considering the recovery ratio, the influence on the cell viability by Puriogen is below 1%, very similar to our previous cell viability analysis after size-based cell sorting . It is noted that the percentage of dead cells is decreased from 15.2 to 7.72%.…”
Section: Results and Discussionsupporting
confidence: 86%
“…Before executing cell wash experiments, polystyrene particles were processed by our device to evaluate the wash efficiency. In our previous work, it has been shown that minimally 400 nm particles were confined in the side flow and hence drawn into the waste . In addition, the size of apoptotic bodies after cell death can be as small as 100 nm .…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations